DESIGNING A MASKMAN BUSINESS MODEL: CLAY FACE MASK FOR MEN - Agnie Hadiati Rasyad; Febriantina Dewi; Siti Jahroh, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Based on the preliminary survey, there was a market need for skin care for men, one of which is face masks. There were limitations to the choice of face-mask products for men in Indonesia. This research aimed to design a verified business model canvas based on the solutions offered to solve consumer problems with face mask products. This research used the customer development method focused on the customer discovery stage and was conducted from January to August 2020 through online questionnaires. The final result of this research is a solution in the form of a prototype face mask product specifically for men following consumer problems and a verified business model canvas. This study presented charcoal clay masks, which have detoxifying benefits to treat and maintain skin health for men. The consumer segment consisted of men with an age range of 20-29 years who live in Jabodetabek. The solution offered by MaskMan has solved consumer problems with face mask products specifically for men. The final sales channel made use of Instagram, Tokopedia, and exhibitions. Based on the test results, consumers needed MaskMan products and were willing to pay for products with a price range of IDR 50,000 - IDR 100,000. The selling price of MaskMan products was IDR 66,500.